Hydrocarbon migration along fault intersection zone — A case study on Ordovician carbonate reservoirs in Tazhong area, Tarim Basin, NW China. (25th July 2016) - Wang, Yangyang; Chen, Jianfa; Pang, Xiongqi; Wang, Gui; Hu, Tao; Zhang, Baoshou; Huo, Zhipeng; Chen, Huayong
Abstract : Understanding hydrocarbon migration mechanism is a key scientific problem that needs to be resolved for effective hydrocarbon exploration in the Ordovician rocks of the Tazhong area, Tarim Basin. Based on analyses of geological setting and reservoir distribution characteristics, hydrocarbon migration process, and mechanisms in the Ordovician, Tazhong area, were investigated by integrating geological, geophysical, and geochemical parameters. Successfully analysed parameters included logging reservoir properties, seismic attributes, production outputs, fluid properties, and hydrocarbon maturity parameters. Results indicate that hydrocarbons were introduced into the Ordovician through a series of charging positions during 3 accumulation periods — middle Caledonian, late Hercynian, and Himalayan. In total 11 hydrocarbon charging positions were identified at intersection zones of the northeast‐trending faults and northwest‐trending flower strike faults. There are anomalies in all parameters on hydrocarbon charging positions. With increasing distance from the charging positions, anomalies of oil density, wax content, dry gas coefficient, hydrogen sulphide content, gas/oil ratio, well production, 4‐/1‐MDBT ratio of crude oil weakened, and natural gas' carbon isotope composition becoming lighter along a northwest to southeast direction are present. Evidence from main hydrocarbon pathway systems theory, formation mechanisms of fault intersection zones, and obvious improvement in reservoir properties at intersection zones supports this viewpoint. Further exploration activities in the Ordovician of the Tazhong area should be conducted in the North Slope's west area, and intersection zones in tectonic up‐dip direction should be emphasized. Copyright © 2016 John Wiley & Sons, Ltd.